Big noisy book of animals - Blackford, Harriet (London: Boxer Books, 2009)
Animals come in all shapes and sizes, from small and fluffy to huge and scaly. In Big Noisy Book of Animals, discover hundreds of amazing facts about animals from all over the globe.